On Ryser's conjecture - Haxell, P; Scott, A (2012)
Motivated by an old problem known as Ryser's Conjecture, we prove that for r = 4 and r = 5, there exists ∈ > 0 such that every r-partite r-uniform hypergraph H has a cover of size at most (r - ∈)v(H), where v(H) denotes the size of a largest matching in H.